Improvement of degradation of Orange G in aqueous solution by Fe2+ added in dielectric barrier discharge plasma system. (June 2022) - Lu, Wei; Sang, Wenjiao; Jia, Danni; Zhang, Qian; Li, Cuihua; Zhang, Shiyang; Zhan, Cheng; Mei, Longjie; Li, Min
Abstract: As a typical azo dye, Orange G (OG) is a potential threat to human health and the safety of water environment. In this study, the effect and mechanism of dielectric barrier discharge (DBD) plasma combined with Fe 2+ on the degradation of OG were explored. The removal efficiency of OG in the DBD/Fe 2+ system was significantly higher than that in the sole DBD system. In the DBD/Fe 2+ system, 93.6% removal efficiency of OG was achieved at an input voltage of 70 V within 10 min, which was much higher than the 56.68% in the sole DBD system. Except for high concentrations of HCO3 − and PO4 3 −, which could promote the degradation of OG in the sole DBD system, SO4 2 −, NO3 − and Cl − could all inhibit the degradation of OG in both the sole DBD and DBD/Fe 2+ system. The radical quenching experiments and the variation of O3 and H2 O2 showed that the addition of Fe 2+ could promote the effective decomposition of H2 O2 into OH, which could improve the removal efficiency of OG. OH was the main active species for OG degradation, at the same time O3 and H2 O2 played important role in both the system. The TOC mineralization efficiency gradually improved with the extension of treatment time. The possible degradation pathways of OG were proposed based on UV–visible spectroscopy and liquid chromatography-tandem mass spectrometry. Graphical abstract: Unlabelled Image Highlights: The addition of Fe 2+ in DBD system promoted the degradation of OG. Various parameters on OG degradation were studied, especially inorganic anions. Fe 2+ could promote the effective decomposition of H2 O2 into OH. Mechanisms and possible OG degradation pathways in DBD/Fe 2+ system were proposed.